A electricidade na cidade de Évora : da Companhia eborense de Electricidade à União Electrica Portuguesa - Matos, Ana Cardoso de (História: revista da Faculdade de Letras da Universidade do Porto, 2018)
Between the late 19th century and the beginning of the 20th century, the production and distribution of electricity became a safer and more effective alternative for public and private illumination and for the supply of motive power. In this context, several entrepreneurial initiatives emerged which aimed at the production and distribution of electricity in different urban centres. In this text, one addresses the emergence and evolution of the Évora Electricity Company (Companhia Eborense de Electricidade), since its formation in the beginning of the 20th century until 1942, when the distribution of electricity to the city of Évora began to be secured by the Portuguese Electrical Union (União Eléctrica Portuguesa).